Research on elderly users' intentions to accept wearable devices based on the improved UTAUT model - Chen, Junxun; Wang, Tao; Fang, Zhenyu; Wang, Hongtao (Frontiers in Public Health, 2023)
[Purpose/significance] As the proportion of the world's elderly population continues to increase, wearable devices can provide ideas for solving a series of problems caused by aging of population. Therefore, it is of great significance for the development of intelligent elderly care and the improvement of the quality of elderly care services to explore the willingness of elderly users to accept wearable devices which provide powerful market research and judgment for businesses, improve the decision-making ability for manufacturers, and enhance the sense of experience of users. [Method/process] This paper studies the purchase intention of wearable devices, an improved UTAUT (unified theory of acceptance and use of Technology) theoretical model is constructed from the perspective of the elderly and new parameters are constructed including four factors related to wearable devices which are Performance Expectation, Perceived Cost, Hedonic Value and Aesthetic Attractiveness and three factors related to the elderly which are Declining Physiological Conditions, Health Anxiety and Personal Information Technology Innovation. This paper empirically studies the influencing factors of elderly users' willingness to accept wearable devices which provide management suggestions for stakeholders. [Result/conclusion] Performance expectation, Perceived Cost, Hedonic Value and Aesthetic Appeal all have a significant impact on the use intention of elderly users. Personal Information Technology Innovation, Physiological Condition Decline, and Use Intention all have an impact on the actual use behavior of elderly users. However, Health Anxiety did not have much effect on use behavior.